2008
DOI: 10.1149/1.2969451
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Transparent nc-InGaO[sub 3](ZnO)[sub 2] Thin Films with Indium mol Ratios Using Solution Process

Abstract: The effect of indium mol ratio on nanocrystalline ͑nc͒-InGaO 3 ͑ZnO͒ 2 thin films prepared by solution was investigated with structural properties. The size of nanocrystallines tended to increase up to 120 nm with an optimized indium mol ratio after second postannealing at 700°C for 10 s with three cycles. The shape of the nanocrystallines and their growth were determined by the indium mol ratio. The main ͑008͒ growth direction, which had a columnar structure, could be retarded by a high indium mol ratio, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The relative intensity of the diffraction peak increased with increasing indium composition, indicating that the crystallinity of the IGZO nanoparticles depended on the indium content. Recently, Kim et al reported that an increase in the indium composition ratio in the solution‐processed nanocrystalline films leads to a decrease in grain size and a loss of crystallinity because the addition of indium obstructs c‐axis growth and cause the lattice strain 21, 22. However, the results in the present study were not in agreement with the results reported by Kim.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…The relative intensity of the diffraction peak increased with increasing indium composition, indicating that the crystallinity of the IGZO nanoparticles depended on the indium content. Recently, Kim et al reported that an increase in the indium composition ratio in the solution‐processed nanocrystalline films leads to a decrease in grain size and a loss of crystallinity because the addition of indium obstructs c‐axis growth and cause the lattice strain 21, 22. However, the results in the present study were not in agreement with the results reported by Kim.…”
Section: Resultscontrasting
confidence: 95%
“…However, the results in the present study were not in agreement with the results reported by Kim. et al This might be due to the difference in growth method, which involved a pulp precursor and the addition of a solution such as 2‐methoxyethanol and monoethanolamine 21, 22. A further investigation of this effect is currently underway.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 In comparison to the vacuum deposition techniques, the use of solution process techniques offers an inexpensive fabrication of active matrix backplanes for large-area display applications. Solution based deposition methods such as spin coating, [5][6][7][8][9] ink-jet, 10,11 and gravure printing 12 have been used in the past few years for the fabrication of a-IGZO TFTs. However, high processing temperature and low device performance restrict the solution-derived a-IGZO TFTs to be used for low cost and high performance electronic applications.…”
mentioning
confidence: 99%
“…Moreover, studies on process developments such as atomic composition ratio, doping, and chemical treatment have remarkably improved TFT performance [ 12 , 13 ]. Among them, in the studies focusing on the atomic composition ratio, the field-effect mobilities in the range 0.5–10.0 cm·V −1 s −1 were controlled by varying the ratio of In:Zn or In:Zn:Ga, and the thickness, roughness, and crystallinity of the semiconductor film were investigated relative to the atomic ratio [ 14 , 15 , 16 ]. Furthermore, a field-effect mobility of over 10 cm·V −1 s −1 was demonstrated using various dopant materials [ 17 , 18 , 19 , 20 ], and a mobility improvement of approximately ten times was achieved by applying chemical treatment or post-treatment [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%